Corporate Social Responsibility disclosure in view of corporate governance - al Quddus, Ayatullah; Meilani, Sayekti Endah Retno (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to empirically prove the effect of corporate governance on Corporate Social Responsibility (CSR) disclosure. The research hypothesis is built based on legitimacy theory and stakeholder theory. The sample selection technique used purposive sampling. A total of 11 banking companies were used as samples with 6 years of research, so the number of observations was 66 observations. Research data processing uses Eviews 10 software by conducting descriptive statistical tests and multiple regression tests with balanced panel data to prove the research hypothesis. The results prove that institutional ownership, independent board of commissioners and the presence of female directors have a negative effect on CSR. The audit committee and the frequency of board meetings have a positive effect on CSR. The size of the board of directors and the board of commissioners has no effect on CSR. The results of this study can be used as a consideration for readers of the company’s annual report, especially investors who are concerned about environmental issues in Indonesia.